1978
DOI: 10.1177/000456327801500176
|View full text |Cite
|
Sign up to set email alerts
|

Plasma 25-Hydroxyvitamin D and Alkaline Phosphatase Isoenzymes in Hyperthyroidism

Abstract: SUMMARY Plasma 25-hydroxyvitamin D (25-0HD) values in 22 hyperthyroid patients did not differ significantly from those of controls matched for age, sex, and the time of year that plasma samples were taken. In the hyperthyroid group, plasma alkaline phosphatase was significantly higher than in controls, and an increase in bone type alkaline phosphatase occurred in 50 %. In the 18 female hyperthyroid patients the plasma y-glutamyl transferase was significantly increased compared with controls. Mean values for pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

1979
1979
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
2
2
0
Order By: Relevance
“…We found no difference in serum 25 OH D3 concentrations in the patients before treatment compared with the controls and there was no significant change after carbimazole therapy. Other studies have also shown similar serum 25 OH D3 concentrations in hyperthyroid patients and control subjects matched for the time of the year that samples were taken (Cleeve & Brown, 1978;Bouillon et al, 1980). Serum 24,25(OH)2D3 concentrations were increased in our patients before therapy, though not significantly.…”
Section: Discussionsupporting
confidence: 79%
“…We found no difference in serum 25 OH D3 concentrations in the patients before treatment compared with the controls and there was no significant change after carbimazole therapy. Other studies have also shown similar serum 25 OH D3 concentrations in hyperthyroid patients and control subjects matched for the time of the year that samples were taken (Cleeve & Brown, 1978;Bouillon et al, 1980). Serum 24,25(OH)2D3 concentrations were increased in our patients before therapy, though not significantly.…”
Section: Discussionsupporting
confidence: 79%
“…Immediately other investigators conducted estimations of 25OHD 3 plasma levels in thyrotoxicosis. Some of them confirmed our findings but others found normal or slightly increased values [4][5][6][7][8][9]. To explain the variety of 25OHD 3 plasma levels in hy-perthyroidism we moved as follow.…”
Section: Methods and Resultssupporting
confidence: 79%
“…Hyperparathyroidism has been found to coexist with thyrotoxicosis in a frequency greater with that of normal population. Parathyroid hormone blood levels have been reported as increased, normal or decreased [26,33], while the mean of alkaline phosphatase levels are significantly raised [4,5,30]. Description of macroscope bone changes are rare, since diagnosis and treatment early are offered for thyrotoxicosis.…”
mentioning
confidence: 99%
“…Reduced 25-OH vitamin D levels have been attributed (Hunstein et al 1977) to an increased metaboism of vitamin D in thyrotoxi¬ cosis. This finding has not however been confir¬ med by all groups (Cleeve & Brown 1978) and in addition the effect of hyperthyroidism on other potent metabolites of vitamin D has not to date been studied. However the reduced intestinal absorption of calcium (Haldimann et al 1980), decreased urinary excretion of phosphorus and increased excretion of calcium (Hendriks 8c Smeenk 1979) is strong presumptive evidence that vitamin D and parathyroid function are suppressed in hyperthyroidism, suggesting that the primary abnormality may be the increased bone résorption.…”
Section: Discussionmentioning
confidence: 90%